Pop-Up Book as a Science Learning Media to Improve Visualization Abilities and Understanding of Science Concepts in SDN Pandanrejo II - Mauidah, Siti; Nusantara, Toto; Arifin, Slamet; Anggraini, Ade Eka; Faizah, Siti (Cetta: Jurnal Ilmu Pendidikan, 2025)
Science concepts are often abstract and difficult to understand through conventional teaching methods. Therefore, a more interactive and concrete approach is necessary. Students frequently struggle to imagine or visualize invisible processes, which can lead to misconceptions or difficulty in grasping the material. The pop-up book, as a learning medium designed to accommodate students’ characteristics and cognitive needs, can serve as a bridge between abstract concepts and concrete experiences. With its three-dimensional elements that appear as the pages are opened, the pop-up book is expected to enhance visual understanding of complex natural phenomena, such as the water cycle, photosynthesis, and the circulatory system. This study is relevant as it aims to systematically examine how the use of pop-up books can improve visualization abilities and understanding of science concepts among elementary school students. The research used a qualitative approach with a descriptive design, involving 23 third-grade students of SDN Pandanrejo II and a teacher as the research subjects. Data were collected through interviews, observations, and documentation analysis to gain an in-depth understanding of students’ and teachers’ experiences in using pop-up books during the learning process. The results show that 80–92% of students reported improvement in learning science through pop-up books. Around 80% of students felt engaged and interested, and found it easier to visualize and remember abstract concepts. Additionally, 85% showed better understanding of difficult concepts and became more active in discussions. About 78% showed improved critical thinking skills, and 82% felt learning became more student-centered. Thus, using pop-up books in science learning proved effective in enhancing students’ ability to visualize abstract and complex scientific concepts.